PERLINDUNGAN TERHADAP INFORMASI PRIBADI ANAK BERKONFLIK DENGAN HUKUM DALAM RUANG DIGITAL - SETYANINGSIH, NI PUTU ARI; Fajar, Ni Made Anggia Paramesthi; Sumertajaya, I Ketut Satria Wiradharma (Fakultas Hukum Universitas Ngurah Rai, 2023)
Children who are in conflict with the law even though they are suspected of havingcommitted a crime, are still entitled to protection by the state. However, in the current digitalera, there are violations of the confidentiality of children’s identities that are in conflict with thelaw. The problems examined in this study regarding the protection of the personal informationof children in conflict with the law in the digital space and the legal consequences if there isdissemination of the personal information of children in conflict with the law in the digital space.In this study using normative legal research methods with statutory approaches,conceptual approaches and case approaches, which then the results found in this study areexplained descriptively.The results of this study are legal protection for children in conflict with the law based onseveral principles, one of the principles is the principle of the best interests of the child which ismanifested in the form of avoiding publication of the child’s identity. Furthermore, the Law on theJuvenile Criminal Justice System stipulates that the identity of a child in conflict with the law mustbe kept confidential in reporting in print or electronic media. Based on this, the disseminationof personal information of children in conflict with the law in digital spaces such as on socialmedia is prohibited by laws and regulations as a form of legal protection for children in conflictwith the law. The legal consequences for someone who is proven to have disseminated personalinformation of a child in conflict with the law in the digital space are criminal sanctions andfines, which can be imposed on individuals and corporations as legal subjects recognized in theJuvenile Criminal Justice System Act